Integrasi Sarasehan Kebangsaan, Hilirisasi Nira, dan Rehabilitasi Pesisir melalui Penanaman Cemara Laut : Rintisan Desa Pancasila Berbasis Asta Cita di Desa Paciran Kabupaten Lamongan - Silkania Swarizona; Nizar Hilmi; Bambang Sigit Widodo; Jauhar Wahyuni; Iman Pasu Purba (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program develops a pilot model of Pancasila Village based on Asta Cita in Paciran Village, Lamongan Regency through the integration of three intervention clusters: (1) national seminar to strengthen Pancasila values ​​and the agenda of “building from the village”, (2) training on downstreaming palm sap as a strengthening of the local economy and entrepreneurship based on village potential, and (3) coastal rehabilitation action through planting sea pine as an environmental adaptation in sandy coastal areas that are vulnerable to wind and erosion. The implementation method uses a participatory and asset-based approach (ABCD) that places residents as the main actors, with a series of activities including socialization, cross-party coordination, training on processing palm sap into value-added products (brown sugar and syrup), seminars with community leaders and academics, planting sea pine, and pre-post evaluation based on knowledge, skills observation, and participant satisfaction. The implementation results show the formation of a cross-generational commitment to make Paciran Village a pilot Pancasila Village, increased community capacity in palm sap processing, and the birth of collective coastal rehabilitation actions. The program also produced sustainability recommendations in the form of routine cross-generational agendas, utilization of village social media for educational content on Pancasila–nira–cemara laut, and the appointment of Pancasila students as environmental sustainability ambassadors in the village.